PENGARUH MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN: PENGUNGKAPAN ISU LINGKUNGAN SEBAGAI VARIABEL PEMODERASI - Sintyawati, Erica Adelia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is (a) to prove the influence of earnings management to the companyâs value; (b) to prove whether the existence of the disclosure of environmental issue which is disclosed by the company will strengthen or weaken the relationship between earnings management and companyâs value. Earnings management is measured by discretionary accrual by using Jones (1991) model. Tobinâs Q is used as the proxy of companyâs value in this research. The disclosure of environmental issue is measured by environmental disclosure index in GRI (Global Reporting Initiative) standard.The samples are manufacturing companies which are listed in Indonesia Stock Exchange. The data is obtained from 2010 â 2012 period annual report of manufacturing companies which are listed in Indonesia Stock Exchange. Samples are obtained by using purposive sampling method. There are 29 manufacturing companies which meet the research sample criteria; thus, 87 observations have been obtained. Multiple linear regression analysis is the statistics method which is used in this research.The result of research shows that: (a) earnings management has no influence to the companyâs value; (b) the disclosure of environmental issue negatively moderated the influence of earnings management to the companyâs value.Keywords: Earnings Management, the Disclosure of Environmental Issue, Companyâs Value